OPTIMALISASI PERSONAL AWARENESS ANAK USIA DINI MELALUI “THE 7 HABITS” Penelitian Tindakan di Kelompok B TK Negeri Pembina Surabaya - Wahyuningtyas, Dessy Putri (Jurnal Warna, 2019)
The purpose of this research is to explain the process and result of applying The 7 Habits method that can optimization personal awareness in group B TK Negeri Pembina Surabaya. This study uses the Kemmis and Mc Taggart procedures which consists of four stages: planning, action, observation, and reflection. The data analysis technique consisted of quantitative and qualitative data analysis. Quantitative data analysis is presented in the form of tables and graphs. While qualitative data analysis using technique according to Miles and Huberman which consists of data reduction, data display, and verification collected through personal awareness instruments, interviews, field notes, and documentation. After the first cycle of action, the average value of 68,47%. Then after second cycle of action, the average value increase to 84,17%. It can be concluded that by using the 7 Habits method can improve personal awareness in children.